Repair of the cerebral dura mater defect by temporalis muscle fascia or peritoneum as autografted tissues in dogs - Osama H. Al-Hyani; Abdullah M. Al-Saiegh; Khalid W. Alheyali (Iraqi Journal of Veterinary Sciences)
This article was designed to compare the efficiency of temporalis muscle fascia or peritoneum as autografted tissues with fibrin glue to reconstruct induced dural defects in dogs. Eighteen adult dogs were used. The animals were divided randomly into two equal groups. The cerebral dura mater induces a defect about (1x 1cm) in diameter in all these experimental animals. The defect was substituted with temporalis muscle fascia in the first group, while in the second group, the defect was substituted by a piece of the peritoneum. The results were evaluated through monitoring postoperative clinical signs, gross features, histopathological changes, and estimation of cerebrospinal fluid pressure with analysis of total cell count, glucose, and protein level of cerebral spinal fluid in both groups at the 15th, 30th, and 60th postoperative days. The experimental animals stayed alive postoperatively without any development of complications primarily related to the appearance of abnormal nervous signs. Grossly, the craniectomy site in both groups was occluded completely, and no cerebrospinal fluid leaks were noticed. Additionally, the dural defect was closed internally, where the grafted tissues were entirely sealed with the dura mater of the host. The histopathological changes were represented by connective tissue proliferation with infiltrations of mononuclear inflammatory cells and angiogenesis. The cerebrospinal fluid pressure, total cell count, glucose level, and protein appeared within the normal range during all experiment periods in both groups. The conclusions of this study can be used in both autograft tissues with fibrin glue to repair dural defects in dogs.